Creating an Immersive Learning Environment for Teaching Agile Scrum and Team Software Process : A Framework for Software Engineering Education - Nurfauza, Jali; Cheah, Wai Shiang; Norazian, Mohd Hamdan; Suriati Khartini, Jali; Lim, Phei Chin; Edzreena Edza, Odzaly; Desmond, Greer (Semarak Ilmu Publishing, 2026)
Most of the principles and concepts that need to be taught in Software Engineering courses are hard to share the realistic experiences because it is difficult to give the student practical exposure to the insight and processes involved. This paper presents an innovative framework tailored for the establishment of an immersive learning environment within the context of a Software Engineering Project course. The overarching objective is to effectively tackle the inherent challenges associated with teaching intricate software engineering concepts, notably Agile Scrum and Team Software Process (TSPi). Conventional pedagogical approaches often prove inadequate in providing a comprehensive and engaging learning experience for students, educatorsandstakeholders. In response, our study introduces a pioneering immersive learning approach, offering a robust solution to this educational gap. To gauge the framework's efficacy and pertinence, we conducted online surveys, specifically targeting third-year students enrolled in the Software Engineering Laboratory course and the project stakeholders involved. These surveys were instrumental in collecting valuable feedback on the practicality and impact of our approach in enhancing the teaching and learning processes. This study presents a thorough exposition encompassing the framework's conceptualization, implementationanditerative evolution. Our research outcomes reveal that our immersive learning approach has successfully met the predefined course objectives, effectively addressing the intrinsic challenge of imparting hands-on experiences associated with software engineering principles and concepts. As a significant contribution to the ongoing initiatives aimed at elevating software engineering education, our study underscores the importance of providing students with tangible exposure to vital concepts such as Agile Scrum and TSPi. Moreover, this paper delineates the collaborativejourney involved in the creation, executionandrefinement of the course framework. Ultimately, our research endeavoursto evaluate the degree to which our innovative framework aligns with the objectives established by both students and stakeholders.